STUDY OF CRANIAL ULTRASOUND FINDING IN HYPOXIC ISCHEMIC ENCEPHALOPATHY IN TERM INFANTS AND ITS CLINICAL CORELATION - Malick, Bijay Laxmi; Murmu, Mangal Charan; Mohanty, Anil Kumar (International Journal of Research -GRANTHAALAYAH, 2018)
Introduction: Incidence of Hypoxic Ischemic Encephalopathy (HIE) is 2-4 per 1000 live birth in USA, 1.8 per 1000 live births in Sweden, 3.8 per 1000 term live births in Australia. In India the incidence of HIE is 10-15 per 1000 live birth. The survivors from severe HIE develop cerebral palsy and mental handicaps as high as 50%. Concurrent use of cranial ultra sound and clinical staging systems are evolving to predict the prognosis. Objective: To study the cranial ultrasonogrphic finding in HIE Infants and its clinical correlation and prediction of outcome. Method: it is a prospective clinical study of 120 baby suffering from hypoxic ischemic encephalopathy. Result: Co-relation of initial cranial ultra sonography grading with mortality and sequel showed an increasing trend as the ultrasonography grading increases, with 51.4% mortality in grade –III, 18.5% in grade-II and 15.4% in grade –I. Seqele 48.6% was observed only in grade-III sonographic abnormality. Conclusion: Sonographic grading is more accurate than the clinical staging in predicting recovery, mortality and sequel.